Mengembangkan Minat Mahasiswa Untuk Berwirausaha Dengan Faktor E-Commerce Dan Pengetahuan Kewirausahaan Studi Kasus Pada Mahasiswa Manajemen Universitas Muhammadiyah Metro - Lelawati, Nina; Fitriani, Fitriani; Sartika, Meilis (Jurnal Manajemen DIVERSIFIKASI, 2023)
Entrepreneurship is an indirect way to overcome poverty. Namely by providing knowledge,skills and fostering entrepreneurial attitudes in job seekers through entrepreneurshipdevelopment. Fostering an entrepreneurial spirit in students is believed to be an alternativeto reducing poverty levels, because graduates are expected to become educated youngentrepreneurs who are able to start their own businesses. Entrepreneurship can not only beused as short-term business tips but also as a general life hack in the long term to createopportunities. in the business sector, for example, companies are successful and obtain greatopportunities because they have creativity and innovation. The aim of this research is to findout whether e-commerce and entrepreneurial knowledge together influence entrepreneurialinterest in management study program students at Muhammadiyah Metro University. This research uses a quantitative approach and the research method used is the Slovin formula.The sample in this research was only taken from 86 students from the class of 2018 at theFaculty of Economics and Business, Muhammadiyah Metro University. The data analysistechniques used are validity test, reliability test, normality test, linearity test. Testing theanalytical model in this research uses multiple linear regression analysis, t test, f test and rdetermination. Based on the results of research using the t test, it was found that e-commercehad an effect on interest in entrepreneurship among students in the management studyprogram at Muhammadiyah Metro University. Knowledge of entrepreneurship has no effectand is not significant on interest in entrepreneurship among students in the managementstudy program at Muhammadiyah Metro University. From the f test, it was found that ecommerce and entrepreneurial knowledge together had a significant effect on interest inentrepreneurship among students in the management study program at MuhammadiyahMetro University.